Опыт реконструкции жилых домов центрального квартала на участке НГС в Нижнем городе Ольвии - Крыжицкий, С.Д. (Боспорские исследования, 2009)
Numerous remains of dwelling houses of Hellenistic time in general have been found during the archaeological digs in the northern part of the Low town of Olbia of late twenty years. Research of these buildings has resulted in a complete account of building up of this part of the town. Reconstruction of planning and volumetrical construction of those dwelling houses has been proposed. The houses of central residential area are of great interest from the point of view of methods of reconstruction and typology of the buildings. The article observes the results of the reconstruction of central residential area dwelling houses. Of course, the given reconstructions of the dwelling houses do not pretend to absolute authenticity. The grade of authenticity of planning reconstruction varies between 0.820 and 0.875.